Analisis Risiko Sebagai Implementasi Sekolah Siaga Bencana Pada Sekolah Dasar - Meliza Astuti; Irsyad; Merika Setiawati (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to describe the Analysis of Risk as an implementation of the SSB program at in Elementary Schools based on preparedness parameters. This type of research study is descriptive qualitative research of which the research subjects are the principal, teachers, students, and employees. The data collection techniques used were observation, interviews, and documentation. The data analysis techniques used in the research study were data collection, data reduction, data presentation, and drawing conclusion. The data validity used was the triangulation of sources and techniques. The results showed that the implementation of SSB SDUA went according to the preparedness parameters. In the aspect o attitude and action, there is knowledge about DRR, the implementation of disaster simulations, ongoing socialization, and having emergency response skills. School policies support DRR, the availability of access to information, knowledge, and training. The aspect of preparedness planning, it was evidenced by the existence of SSB assessment documents, action plans before, during and after disasters, PROTAP, disaster warning systems, and evacuation sites. The aspect of resource mobilization was evidenced by the existence of a school disaster alert group, monitoring, and evaluation conducted by the school, the availability of equipment, supplies, and post-disaster basic needs. Supporting factors for SDB SSB program are qualified human resources and related agencies, while the impeding factors were related to the extent of school area that is quite narrow and the equipment have yet to cover all of school resident needs.